Investigation on the effect of different friction stir machining tools shape on the mechanical properties of magnesium alloy work piece - N., Abdul Wahab; Fatchurrohman, Nanang; Z., Zulkfli (IOP Publishing Ltd., 2021)
Friction stir process (FSP) is a method of solid-state consolidation that uses an inexhaustible tool to increase the modification of work piece structural. This current work presents a study of friction stir process on magnesium (Mg) alloy work piece using different design of pin profiles tool. Experiments were conducted in dry condition where tool progression was monitored carefully in every milling passes, then the effect and quality criterion were measured. Result shows that the dominant tool of friction stir process mechanism of mild steel tool is the strength intensity increased at higher speed and lower plunge length due to the superiority of friction stirred region on the magnesium. Furthermore, the hardness of the stirred friction of Mg alloy also increased by using a triangle pin profile design.